FAIRY TALES AND MEDIATIONAL PRACTICE: POSSIBILITIES TO BUILD COGNITIVE REPERTOIRE IN CHILDHOOD EDUCATION - Ferreira, Juliene Madureira; Vectore, Celia (Olhares & Trilhas, 2015)
Exploratory study, aiming to verify the possible effects of a practice mediated, from the use of fairy tales, in the construction of cognitive repertoire, in pre-school children, as provided for in the instrument "Dynamic assessment and intervention: Improving children's narrative abilities". Participated in the survey, five children of five years. For the collection of data, weekly workshops were organized, total of six. Mediation was performed considering the mediation criteria, "focus, expansion, affectivity, reward and regulation of behavior". The work was divided into four steps: (1) rapport and presentation of fairy tale without mediation; (2) design and pre-test assessment; (3) presentation of fairy tale with mediation) and (4) drawing and post-test evaluation. The comparison of the results reveal that mediation, through the narrative of fairy tales, can be an important strategy for building cognitive repertoire with children, once all the items assessed student Protocol form have undergone positive changes by the end of the work.